Evaluation de l'état de stock de quelques débarquements par les chaluts des ressources halieutiques du port de Salamandre, Mostaganem - LAHLAH, Mourad; BOUNEDJAR, Adnan (My University, 2023)
This work aims to study the state of catches and stocks of certain species of fish caught by fishing trawlers in the port of Salamandre, province of Mostaganem, during the period from 2013 to 2023. The results obtained showed that there has been a disruption of fishing activity in recent years and a slight increase in the number of trawlers in the fishing fleet of the port of Salamandre. The results also showed the predominance of blue fish in the landing process compared to other groups, with the dominance of sardines, as the CPUE analysis showed that sardines have the highest values compared to other species and Scheffer's method confirmed the dominance of sardines over other species.
Keywords: Fishing; trawler; fish; port of Salamandre; Mostaganem